Arifî Paşa'nın Seyahatnamesi Diyarbekir Seyahati - Öztürk, Mustafa; Yılmazçelik, İbrahim (Türk Tarih Kurumu [EN], 1997)
Mahâlli tarih araştırmalarında arşiv kaynakları ile genel nitelikli eserlerin değeri inkâr edilemez. Ancak bu kaynaklarda gözden kaçmış ve resmiyete intikal etmemiş teferruata ait bilgiler bulunmayabilir. Bu bilgileri şimdiye kadar değerlendirilmeyen veya üzerinde pek fazla durulmayan seyahat-namelerde bulmak mümkündür. Arifi Paşa'nın Diyarbakır seyahati bu bakımdan önemlidir. Bölge hakkında yukarıda değinilen resmi kayıtlara geçmemiş pek çok bilgi ve gözlemi ihtiva etmektedir. Yalnız bu gibi eserleri kullanırken tarih tenkit usullerini ihmal etmemek gerekir. Nihayet söz konusu gözlemler ve bilgiler, seyyahın o andaki gözlemleri, dikkatini çeken hususlar ve görmek istediği, kendi düşüncesine göre nakletmekte fayda gördüğü değerlendirmelerdir. Her şeye rağmen gene de bölge hakkında önemli bilgiler vermektedir. Eseri bu nazarlarla değerlendirmek daha doğru olacaktır.

The value of archival sources and general reference works in local historiography is undeniable. However, such sources may lack certain details that either escaped official attention or were never formally recorded. Information of this kind can often be found in travelogues, which have not yet been sufficiently examined or have received limited scholarly attention. In this respect, Arifî Pasha’s journey to Diyarbakır is particularly significant. His account contains numerous observations and pieces of information about the region that are not reflected in the aforementioned official records. Nonetheless, when using works of this nature, it is essential not to neglect the methodological principles of historical criticism. Ultimately, the observations and data presented in such travel narratives reflect the traveler’s immediate impressions, the aspects that captured his attention, and the elements he deemed worthwhile to report based on his own perspective. Despite these considerations, the work still provides valuable insights into the region. Therefore, evaluating the text with these critical perspectives in mind will yield a more accurate and balanced understanding.
Arifî Pasha’s Travelogue: The Journey to Diyarbekir
Keywords: General Turkish History (Other); Genel Türk Tarihi (Diğer)